2021
DOI: 10.3390/ma14216642
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Blood Clot in Guided Bone Regeneration: Biological Considerations and Clinical Applications with Titanium Foil

Abstract: In Guided Bone Regeneration (GBR) materials and techniques are essential to achieve the expected results. Thanks to their properties, blood clots induce bone healing, maturation, differentiation and organization. The preferred material to protect the clot in Guided Bone Regeneration is the titanium foil, as it can be shaped according to the bone defect. Furthermore, its exposition in the oral cavity does not impair the procedure. We report on five clinical cases in order to explain the management of blood clot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 74 publications
1
9
0
Order By: Relevance
“…In an in vivo study, Lambert and colleagues [ 16 ] investigated double sinus lift procedures using blood clot, autogenous bone chips or bovine hydroxyapatite (BHA), finding that the bone formation occurred with all three of the space fillers. Many studies have recently reported several clinical cases, which were supportive of the usefulness of titanium foil barriers along with blood clots and were in agreement with our results, demonstrating the role of titanium in clot protection during GBR procedures [ 12 , 14 , 15 , 17 , 18 , 19 ].…”
Section: Introductionsupporting
confidence: 92%
“…In an in vivo study, Lambert and colleagues [ 16 ] investigated double sinus lift procedures using blood clot, autogenous bone chips or bovine hydroxyapatite (BHA), finding that the bone formation occurred with all three of the space fillers. Many studies have recently reported several clinical cases, which were supportive of the usefulness of titanium foil barriers along with blood clots and were in agreement with our results, demonstrating the role of titanium in clot protection during GBR procedures [ 12 , 14 , 15 , 17 , 18 , 19 ].…”
Section: Introductionsupporting
confidence: 92%
“…The clot plays a key role in GBR, and its protection during its maturation process is essential to obtain good bone quality for successive implant insertion [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…Among the existing fillers used under the occlusive barriers [ 14 , 15 ], blood clots mixed with beta-tricalcium phosphate seems to be the most suitable [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…The critical role of blood clots in wound healing and fracture repair has been well-studied (Shiu et al 2018). In bone repair, blood clots form a temporary matrix that initiates bone formation through the influence of soluble factors (growth factors, cytokines, inflammatory factors, coagulation factors, and antimicrobial agents), cell recruitment, and their migration through the fibrin network (Milillo et al 2021). Using Sal instead of aspirin is likely beneficial because the formation of blood clots is necessary to start the repair mechanisms in the tissue.…”
Section: Discussionmentioning
confidence: 99%